Battling antimicrobial resistance: new guidance and insights - Moore, David P (The Lancet infectious diseases, 2025)
Antimicrobial resistance (AMR) in bacteria commonly implicated in hospital-associated and some community-associated infections is a major public health threat, with 1·91 million deaths attributable to AMR bacterial infections projected in 2050, most of which (>65%) will occur in people older than 70 years. 1 Rates of hospital-associated sepsis vary from 13·8 to 175·0 per 100 000 adult population per year, with mortality in over half of those affected. 2 Almost 60% of episodes of hospital-associated sepsis, usually attributed to AMR organisms, occur in neonates, with rates among neonates treated in intensive care units estimated at 112·9 per 1000 cases, also with a high mortality risk. 2 The burden of AMR bacterial infection disproportionately affects low-income and middle-income country (LMIC) settings. 1,2 The pioneering coordinated effort to derive a comprehensive list of AMR bacteria for global public health intervention purposes was undertaken by WHO in 2017 through the release of its first Bacterial Priority Pathogens List (BPPL). The authors used similar methodologies to those used in the 2017 BPPL derivation, with extension of factors contributing to the weighting of each AMR organism under consideration based on recent advances in understanding of the burden and epidemiology of AMR bacterial infections. 1 Notable findings in the establishment of the 2024 WHO BPPL include the following: (1) retention of antibiotic-resistant Gram-negative pathogens (carbapenem-resistant Klebsiella pneumoniae, third-generation cephalosporin-resistant Escherichia coli, and carbapenem-resistant Acinetobacter baumannii) in the top tier of the priority list, underpinned by their considerable contribution to disease burden, morbidity, and mortality in all settings; (2) addition of rifampicin-resistant Mycobacterium tuberculosis to the list of priority pathogens; (3) increased emphasis on fluoroquinolone-resistant Salmonella enterica serotype Typhi, Shigella spp, and Neisseria gonorrhoeae as contributors to the burden of disease, particularly in LMICs; and (4) deprioritisation of penicillin-non-susceptible Streptococcus pneumoniae and vancomycin-resistant Staphylococcus aureus from the list. Provision of soap and water to communities significantly reduces the burden of common childhood infections, 9 while adherence to hand washing reduces by 50% the rate of maternal mortality following childbirth. 10 Although there is a dearth of high-quality evidence on how optimisation of infection prevention and control measures might affect the burden, incidence, and health-care costs of hospital-associated infections, the onus is on all health-care workers to minimise the potential for transmission of AMR organisms from our hands to our patients.